STUDI ADSORPSI ZAT WARNA NAPHTHOL YELLOW S PADA LIMBAH CAIR MENGGUNAKAN KARBON AKTIF DARI AMPAS TEBU - Utomo, W. P.; Santoso, E.; Yuhaneka, G.; Triantini, A. I.; Fatqi, M. R.; Huda, M. F.; Nurfitria, N. (Jurnal Kimia (Journal of Chemistry); Vol.13 No.1 Januari 2019, 2019)
The aim of this research is to get activated carbon from sugarcane bagasse with high adsorption capacity to Naphthol Yellow S and to know factors influencing the adsorption capacity. Activated carbon is prepared by incomplete combustion of sugracane bagasse. The resulting carbon is activated with H 2 SO 4 with concentration variation of 0.5; 1.0; 1.5 and 2.0 M and is continued by calcination at 400 °C. The measurement of the surface area of ??activated carbon by the methylene blue method indicates that the activation process successfully extends the surface area of carbon from 31.87 m 2 /g before activation to 66-72 m 2 /g after activation. Activated carbon with concentration of 2.0 M H 2 SO 4 showed the highest surface area of ??71.85 m 2 /g, however, the best adsorption was shown by activated carbon with a concentration of 0.5 M H 2 SO 4 with the adsorption capacity of 83.93%. The adsorption test showed that the best amount of adsorbent was 0.2 g with contact time for 30 minutes. Prolonged contact time can decrease the amount of Naphthol Yellow S adsorbed. The best adsorption test result was shown by sample with activator concentration of 0,5 M, mass of 0,2 g and contact time of 30 min with adsorption capacity 95,81% or amount of dye adsorbed equal to 143,72 mg/g. The adsorption study also showed that the entire Naphthol Yellow S adsorption process followed the Langmuir isothemal adsorption model. Qualitative testing of real batik waste indicates that activated carbon can reduce the dyes waste containing Naphthol Yellow S exhibited by the color of batik waste which is more faded.